Translation and Validation of Telugu Version of Marital Satisfaction Scale (T-MSS) - Vishwas, Hunsur Nagendra; Reddy, Jillella Sandeep; Katravath, Pradeep Kumar; Posanpally, Naveen Kumar; Bojja, Prasanna Kumar; Gattikoppula, Harish (Indian Journal of Pharmacy Practice)
Introduction: Interest in studying marriage-related issues has increased in recent years. Researchers have demonstrated a constant decrease in marital satisfaction over time in married couples. Marital Satisfaction Scale (MSS) can be used to examine how marital satisfaction affects couple’s well-being; A MSS was developed in Pakistan showing good reliability and internal consistency. Objevctive: Present study aimed to translate and validate MSS to Telugu (T-MSS) language. Methods: Present study implemented standard methodology for Translation, Adaptation and Validation of instruments for use in cross-cultural healthcare research along with World health organization process of translation and adaptation of instruments. Results: 141 first-married individuals participated in the present study to assess validity, internal consistency and reliability. Cronbach alpha (α) of T-MSS was 0.863 demonstrating good validity and internal consistency, Pearson product moment coefficient of correlation (r) was found to be 0.845 and Cohen's kappa (κ) was found to be 0.759 demonstrating good test-retest reliability. Conclusion: T-MSS is a useful tool in Telugu language demonstrating good reliability and internal consistency. It can be utilized in diverse settings like social and clinical research to assess various factors related to marital satisfaction.
Keywords: India; Marital Satisfaction; Marital satisfaction scale; Telugu; Translation & Validation; T-MSS